Brazilian Biodiversity Fruits: Discovering Bioactive Compounds from Underexplored Sources - Biazotto, Katia Regina; De Souza Mesquita, Leonardo Mendes; Neves, Bruna Vitória; Braga, Anna Rafaela Cavalcante; Tangerina, Marcelo Marucci Pereira; Vilegas, Wagner [UNESP]; Mercadante, Adriana Zerlotti; De Rosso, Veridiana Vera (American Chemical Society (ACS), 2019)
Large segments of the Brazilian population still suffer from malnutrition and diet-related illnesses. In contrast, many native fruits have biodiversity and are underexploited sources of bioactive compounds and unknown to consumers. The phytochemical composition of nine underexplored Brazilian fruits was determined. Carotenoids and anthocyanins were identified and quantified by high performance liquid chromatography-photodiode array-tandem mass spectrometry (HPLC-PDA-MS/MS), and phenolic compounds and iridoids were identified by flow injection analysis-electrospray-ion trap-tandem mass spectrometry (FIA-ESI-IT-MS/MS); in total, 84 compounds were identified. In addition, the chemical structure and pathway mass fragmentation of new iridoids from jenipapo (Genipa americana) and jatoba (Hymenae coubaril) are proposed. The highest level of carotenoids was registered in pequi (Caryocar brasiliense; 10156.21 μg/100 g edible fraction), while the major total phenolic content was found in cambuci (Campomanesia coubaril; 221.70 mg GAE/100 g). Anthocyanins were quantified in jabuticaba (Plinia cauliflora; 45.5 mg/100 g) and pitanga (Eugenia uniflora; 81.0 mg/100 g). Our study illustrates the chemical biodiversity of underexplored fruits from Brazil, supporting the identification of new compounds and encouraging the study of more food matrixes not yet investigated.
Keywords: anthocyanins; Brazilian fruits; carotenoids; chemical biodiversity; iridoids; phenolic compounds